Investigation of Trace and Toxic Metal Elements in Some Types of Meat, Fish and Their Products in the Markets of Damascus (Damascus University Journal of agriculture sciences, 2025)
The study was conducted at the laboratories of the Department of Food Sciences, Faculty of Agriculture, University of Damascus, and the National commission for Biotechnology in 2021-2022, and aimed to estimate some trace metal elements such as iron (Fe), zinc (Zn), copper (Cu), manganese (Mn) and selenium (Se) and some heavy or toxic metal elements such as cadmium (Cd), lead (Pb), and chromium (Cr) in some types of meat and meat products in the Syrian market. 5 samples of veal thigh meat, 8 samples of minced veal, 8 samples of minced lamb meat, 7 samples of chicken breast, 7 samples of chicken thighs, 5 samples of canned sardines, 5 samples of mullet fish, in addition to some types of meat products, 6 samples of veal sausages, 4 samples of pastrami, 12 samples of chicken mortadella. The samples were mixed to form a uniform sample, and then the mineral elements were estimated using the Atomic absorption spectroscopy.The results showed that the samples of pastrami, mullet, minced veal and veal thighs exhibited higher values ​​of iron and zinc content than the processed products and chicken meat, and the fish samples excelled in selenium content. Moreover, the results showed that all samples conformed to the Syrian standard specifications in the content of the studied toxic metal elements.
Keywords: Meat; Fish; Minerals; Atomic absorption